Transferrin as a marker of pulmonary maturation in lambs born at term or premature - Baptista, R. S. [UNESP]; Bovino, F.; Denadai, D. S. [UNESP]; Rahal, N. M. [UNESP]; Perri, S. H.V. [UNESP]; Lucas, F. A. [UNESP]; Feitosa, F. L.F. [UNESP]; Peiró, J. R. [UNESP]; Mendes, L. C.N. [UNESP] (FapUNIFESP (SciELO), 2019)
The aim of this study was to search for acute phase proteins that could indicate signs of maturation in the premature neonate by quantifying them in serum. Immunoglobulin A, ceruloplasmin, haptoglobin, acid glycoprotein, tranferrin, albumin, light and heavy chain immunoglobulin G were quantified, comparing the profile of proteinograms from term to preterm lambs submitted to different protocols that stimulate respiratory activity. Six groups were used: PN (n= 9): born from normal birth; CN (n= 7): born from caesarean section at normal time of gestation; CP (n= 6): born from premature cesarean without any type of treatment; DEX (n= 9) preterm whose mothers received prepartum dexamethasone; SURF (n= 6) preterm treated with surfactant; DEXSURF (n= 6): preterm treated with surfactant whose mothers received prepartum dexamethasone. The evaluations were performed immediately after birth (M0), after 24 and 48 hours (M24 and M48). Samples were processed with sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). Albumin, immunoglobulins, and serum total protein of the lambs were elevated, after colostrum ingestion. Higher serum transferrin values refer to a longer gestational period, and this protein may be used as a marker of neonatal maturation.
Transferrina como marcador de maturação pulmonar em cordeiros nascidos a termo ou prematuros
Keywords: Eletrophoresis; Neonatology; Protein concentration; SDS-PAGE; Sheep